Empowered batch 3 IIUM mkitchen students - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Mahri, Nurhafizah; Ismail, Amelia Ritahani; Abdul Kadir, Andi Fitriah; et al. (mKitchen, 2022)
This book narrates the journey of empowering Batch 3 IIUM mKitchen Students with the 3Es (Employment, Empowerment, and Entrepreneurship). The students started the journey with in-class training on entrepreneurship, business plan development, digital marketing, and cash management. Then, the students had a cooking demonstration on several foods trained by trainers of mKitchen. This batch is fortunate to have a permanent space given by the university. JEL Classification: M13 and M15